Assessing the perceived indoor acoustic environment quality across building occupants in a tertiary-care public hospital in Singapore. (15th August 2022) - Lam, Bhan; Fan, Esther Monica Peijin; Ooi, Kenneth; Ong, Zhen-Ting; Hong, Joo Young; Gan, Woon-Seng; Ang, Shin Yuh
Abstract: Although hospitals are notorious for poor acoustics, the acoustic environment is usually evaluated in silos, or in conjunction with few indoor environmental quality (IEQ) factors. With only anecdotcal evidence, it is important to first establish a holistic baseline perception of the hospital acoustic environment before commissioning costly measurement campaigns. A psychometric questionnaire based on the industry-standard IEQ survey and ISO 12913-2 soundscape standard was administered to examine the perceived indoor acoustic environment quality across major occupant groups (i.e. staff, patients, visitors) in an acute hospital in Singapore. Of the 16 IEQ factors examined, all occupant groups expressed the greatest dissatisfaction with noise levels and sound privacy. Notably, the staff were significantly more dissatisfied than the other groups in terms of sound privacy and overall IEQ. When assessing the overall quality (OQ) and appropriateness (OA) of the acoustic environment, OQ was similarly neutral across all groups, whereas the staff expressed significantly lower OA than both patients and visitors. The dissatisfaction in the acoustic environment could be attributed to the perceived dominance and annoyance of vocal and operational sounds across all occupant groups, as well as the environment set-up with most being housed in cohort rooms. Particularly, the staff were significantly more annoyed with vocal and operational sounds than patients and visitors. This study also yielded evidence that challenges the validity of the 5-item Weinstein noise sensitivity scale when used in an Asian context, as well as the applicability of the perceived affective quality circumplex model in ISO 12913-3 for indoor environments. Graphical abstract: Image 1 Highlights: All hospital occupants were most dissatisfied with sound privacy and noise levels. Vocal and operational sounds were the most dominating and annoying for all occupants. Staff were significantly more annoyed than patients and visitors across all sound types. Five-item Weinstein noise sensitivity scale not reliable in the Asian context. Circumplexity of perceived affective quality model not valid in indoor environments.